As questões de gênero sob as lentes do cinema : uma análise a partir do filme "Hoje eu quero voltar sozinho" - Silva, Monara Santos (2017)
The present dissertation aimed to problematize and understand the gender relations through the film "Today I want to return alone" (2014), fiction directed by the filmmaker Daniel Ribeiro, as a tool of education under the bias of the filmic analysis. The film tells the story of the blind teenager, Leonardo (Guilherme Lobo), who, through the discoveries and curiosities typical of his age and in search of his own identity, finds himself in love with a new class student. However, being blind and homosexual does not define it. They are only characteristics of a young man who has fears and doubts like any other of his age. As a research method, the film analysis was used, respecting the phases of decomposition and reconstruction. The data were organized from two thematic axes - homosexuality and gender normativity - with the intention of thinking about how the contemporary cinematographic productions are meaning some themes that revolve around the problematic of the body and its manifestations of identity, ethical-moral and political , In the sense of designing social practices of gender. The results of the analyzes indicate that the film's proposal continues to present the creation of new archetypes, at the moment when it exhibits a radical redefinition and redistribution of gender in that it indicates that the male body can feel desire / affection for another body of the same sex Without presenting feminine characteristics, transforming the action of macho gender present in society.